Structure and bonding in ionized water clusters - Do, Hainam; Besley, Nicholas A. (American Chemical Society, 2013)
The structure and bonding in ionized water clusters, (H_2O)n+(n = 3–9), has been studied using the basin hopping search algorithm in combination with quantum chemical calculations. Initially candidate low energy isomers are generated using basin hopping in conjunction with density functional theory. Subsequently, the structures and energies are refined using second order Moller-Plesset perturbation theory and coupled cluster theory, respectively. The lowest energy isomers are found to involve proton transfer to give H_3O+ and a OH radical, which are more stable than isomers containing the hemibonded hydrazine-like fragment (H_2O-OH_2), with the calculated infrared spectra consistent with experimental data. For (H_2O)_9^+ the observation of a new structural motif comprising proton transfer to form H_3O^+ and OH, but with the OH radical involved in hemibonding to another water molecule is discussed.